Penggunaan Media Pop Up Book Untuk Meningkatkan Minat Baca Dalam Pembelajaran Bahasa Indonesia Materi Dongeng Pada Siswa Kelas III SDK 077 Kewapante - Maria Herlina Sunarti; Maria Helvina; Marianus Yufrinalis (Journal on Education, 2023)
This study aims to increase reading interest in learning Indonesian material for fairy tales in class III SDK 077 Kewapante. This research is a class action research (CAR) using Kurt Lewin's research flow which was carried out for two cycles, where each cycle consisted of 4 meetings consisting of four stages, namely the planning stage, the implementation stage, the observation stage, and the reflection stage. The subjects in this study were class III students at SDK 077 Kewapante, totaling 28 students consisting of 21 boys and 7 girls. Data analysis techniques in this study used quantitative data analysis techniques, namely learning test results and qualitative data analysis techniques in the form of observations and questionnaires. Data collection techniques in this study used observation, questionnaires, tests, and summaries. The results of the study using pop up book media showed that there was an increase in students' reading interest in learning Indonesian material for fairy tales as evidenced by an increase in the average value of students' reading interest in cycle I of 78.66% with a proportion of completeness of 80.35% and in cycle II experienced an increase with an average score of students' reading interest of 87.31% with a completeness proportion of 92.85%. This shows that the use of pop up book media is one of the media that can be further applied in the learning process in class in learning Indonesian to increase students' interest in reading in class III SDK 077 Kewapante..